Radionuclide study in gastroparesis: Is it still relevant? - Abdul Rahim, Mohamad Shahrir; Shuaib, Ibrahim Lutfi bin; Ahmad Sarji, Sazilah binti (IIUM Medical Journal Malaysia, 2016)
The incidence of gastroparesis in Malaysia is not well documented. Gastroparesis may present with various combinations of debilitating sign and symptoms that decrease quality of life and increases morbidity. It is diagnosed based on clinical symptoms and exclusion of the obstruction. There should be a high index of suspicion in patients who present with symptoms to avoid missing the diagnosis. There are various approaches to study the gastric motility. Here’s a case of a young adult woman with type 1 diabetes mellitus suffering severe gastrointestinal symptoms. In this case, radionuclide scintigraphy is used as one of the investigation to confirm the diagnosis of gastroparesis. Radionuclide scintigraphy remains a hallmark in the diagnosis of gastroparesis after excluding mechanical obstruction.